Robust Hybrid Current Controller for Permanent-Magnet Synchronous Motors - Al-kaf, Hasan Ali Gamal; Lee, Kyo Beum (Journal of Electrical Engineering and Technology, 2023)
In recent years, hybrid models have been widely used for various power electronic appliances. The principal idea of hybrid model is to combine the merits of each control method to achieve better overall performance. However, switching between controllers remains a challenging problem that requires robust switching techniques to ensure smooth transition between controllers. Existing switching techniques tend to cause undesired bumps, oscillations, and large overshoots in the motor drives. Therefore, this study proposes a robust hybrid model that combines field-oriented control and model predictive control (MPC) using the cost function of MPC for permanent-magnet synchronous motors fed by a two-level inverter. In addition, space vector pulse width modulation is used to guarantee a constant switching frequency. The results show that the proposed hybrid model has fast dynamics, zero steady state error, small overshoot and constant switching frequency. In addition, the results reveal that the hybrid model provides good performance and outperforms conventional hybrid method in different operating cases. Simulation and experimental results demonstrate the effectiveness of the proposed hybrid model.
Keywords: Constant switching frequency; FOC; Hybrid currents; Hybrid model; Model-predictive control; Performance; Permanent Magnet Synchronous Motor; PMSM; Switching techniques; Two-level inverters; FOC; Hybrid model; MPC; PMSM; Two-level inverter